SENI SUARA DAERAH SEBAGAI MEDIA PENDIDIKAN APRESIASI SENI - Isti Kurniatun (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2004)
This research 'on the art of Javanse singing as education ill art appreciation thought in Elementary Schools ill Surakarta aims to discover all incongruity between. the goals of the Local Curriculum and its implementation. The incongruity can be found until the recent time, and therefore the goals of the Local Curriculum, which is perserving national culture totally unsucceeds. The art observers, academics and relevant institution have to react concretly to anticipate these konditions in order to succeed the goals of the Local Curriculum.Key words: Javanese singing, education, art appreciation, Elementery Schools